Translating Figurative Language Using Song Lyrics - Axel Alessandro Satriawan (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
Nowadays translators are challenged not only to be able conveying the message from source language (SL) totarget language (TL) but also they are demanded to bridge cultural differences through language. That is why translator needs to choose the best diction in order to maintain meaning and expression from SL to TL without forgetting the aesthetic. Losing the meaning of word due to the translators lack ability might give bad impression. In Asian context, English is a foreign language, so translating English to TL is totally difficult. Using song lyrics as one of translating strategy, especially to deal with figurative language could be one of the alternative way in maintaining the meaning and expression in translation. Students face song lyrics in their daily life so they are learning while having fun.This study is about using song lyrics to help students understanding in translating figurative language from SL to TL, and to help them grasp the meaning from figurative language with their own cultural background. Using song lyrics for translating figurative language as the base reference also help them to be more sensitive about the meaning and improve their analysing skill because figurative language consists of many types of word which their meanings are different with the literal interpretation. Moreover, translating in the 21st century needs great innovation to face the challenges in learning English as a foreign language.